What is the best age to enter the labor market in Brazil today? - Marcelo Justus; Henrique Kawamura; Ana Lúcia Kassouf (EconomiA, 2015)
This study is an attempt to measure the effects of entering the Brazilian labor market at an early age on wages earned as an adult. In a previous study using a pooled data cross section (1988 and 1996), the conclusion was reached that the effect of entering the labor market at an early age is negative for those who begin to work early in life, but it becomes positive for those who start working between the age of 12 and 14. We used a pooled data cross section (2001-2009 and 2011) and found evidence that this age is much higher today, meaning that earnings continue to grow as people enter the labor market after the age of 14. We also found a threshold effect in returns to education with a magnitude that increases as people enter the labor market at older ages. – – Este estudo é uma tentativa de medir os efeitos da entrada precoce no mercado de trabalho brasileiro nos salários na fase adulta da vida. Um estudo anterior feito com dados empilhados (1988 e 1996) concluiu que o efeito da idade de ingresso no mercado de trabalho é negativo para quem começa a trabalhar muito cedo, mas torna-se positivo para quem começa a trabalhar com idade entre 12 e 14 anos. Usamos dados empilhados (2001-2009 e 2011) e encontramos evidências de que atualmente essa idade é bem maior, ou seja, que os rendimentos continuam a crescer com a postergaç\~ao do ingresso no mercado de trabalho além dos 14 anos. Encontramos também um efeito limiar nos retornos em escolaridade, cuja magnitude cresce à medida que a entrada no mercado de trabalho é postergada.
Keywords: J31; O12; 330; Child labor; Earnings; Education